A betabaculovirus encoding a gp64 homolog. (December 2016) - Ardisson-Araújo, Daniel; Pereira, Bruna; Melo, Fernando; Ribeiro, Bergmann; Báo, Sônia; de A. Zanotto, Paolo; Moscardi, Flávio; Kitajima, Elliot; Sosa-Gomez, Daniel; Wolff, José
Abstract Background A betabaculovirus (DisaGV) was isolated fromDiatraea saccharalis (Lepidoptera: Crambidae), one of the most important insect pests of the sugarcane and other monocot cultures in Brazil. Results The complete genome sequence of DisaGV was determined using the 454-pyrosequencing method. The genome was 98, 392 bp long, which makes it the smallest lepidopteran-infecting baculovirus sequenced to date. It had a G + C content of 29.7 % encoding 125 putative open reading frames (ORF). All the 37 baculovirus core genes and a set of 19 betabaculovirus-specific genes were found. A group of 13 putative genes was not found in any other baculovirus genome sequenced so far. A phylogenetic analysis indicated that DisaGV is a member ofBetabaculovirus genus and that it is a sister group to a cluster formed by ChocGV, ErelGV, PiraGV isolates, ClanGV, CaLGV, CpGV, CrleGV, AdorGV, PhopGV and EpapGV. Surprisingly, we found in the DisaGV genome a G protein-coupled receptor related to lepidopteran and other insect virus genes and agp64 homolog, which is likely a product of horizontal gene transfer from Group 1 alphabaculoviruses. Conclusion DisaGV represents a distinct lineage of the genusBetabaculovirus . It is closely related to the CpGV-related group and presents the smallest genome in size so far. Remarkably, we found a homolog ofgp64, which was reported solely in group 1 alphabaculovirus genomes so far.